2019
DOI: 10.21608/jappmu.2019.59995
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of Estrus and Ovulation Using CIDR and Prostaglandin for Improving Pregnancy Rate of Repeat Breeder Egyptian Buffaloes

Abstract: To synchronize estrus and ovulation for improving pregnancy rate (PR) of repeat-breeder buffaloes, Controlled Internal Drug Release (CIDR) + prostaglandin (PGF2α) was used before service of repeat breeder buffaloes. Total of 20 cyclic lactating buffalo-cows (4-7 years, 400-500 kg, non-pregnant up to 90postpartum day) and 10 cyclic buffalo-heifers (2.5-4 years, 350-400 kg, not conceived after 3 services) were used in this study. In the 1 st group, a CIDR was inserted for 9 days, regardless reproductive status, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The P 4 profile observed at estrus may indicate higher pregnancy rate of cows in G3. Several authors indicated this finding (Abdel-Khalek et al, 2018;Abo-Farw et al, 2019). It is well known that P 4 showed an elevation during pregnancy, thus increment P 4 profile at 120-d postpartum in cows treated with bentonite (G3) was in relation with conceiving all cows in G3 versus 80 and 50% in G2 and G1, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…The P 4 profile observed at estrus may indicate higher pregnancy rate of cows in G3. Several authors indicated this finding (Abdel-Khalek et al, 2018;Abo-Farw et al, 2019). It is well known that P 4 showed an elevation during pregnancy, thus increment P 4 profile at 120-d postpartum in cows treated with bentonite (G3) was in relation with conceiving all cows in G3 versus 80 and 50% in G2 and G1, respectively.…”
Section: Discussionmentioning
confidence: 93%